Geum japonicum Thunb. exhibits anti-platelet activity via the regulation of cyclic guanosine monophosphate - Lee, Yuan Yee; Akram, Abdul Wahab; Kim, Young-Hee; Irfan, Muhammad; Kim, Sung Dae; Saba, Evelyn; Kim, Tae Wan; Yun, Bong-Sik; Rhee, Man Hee (Frontiers in Pharmacology, 2025)
IntroductionTraditionally, Geum japonicum Thunb. (GJ) extract has been used to treat headaches and dizziness. We hypothesize that GJ exhibits anti-platelet activity that may prevent ischemic events to alleviate these symptoms. In this study, we investigated the anti-platelet activity of GJ as a potential mechanism for enhancing blood flow and preventing vessel occlusion.MethodsPlatelets were stimulated with collagen, adenosine diphosphate (ADP) or thrombin. Platelet aggregation was carried out using a platelet aggregometer with washed platelets from Sprague-Dawley rats. We observed the mobilization of calcium ions using Fura-2AM and adenosine triphosphate (ATP) release via a luminometer. The activation of integrin αIIbβ3 and population of platelet-neutrophil aggregates (PNAs) were investigated using flow cytometry. Platelet shape change was observed using scanning electron microscopy and transmission electron microscopy.ResultsGJ extract inhibited collagen, ADP and thrombin-induced platelet aggregation. It effectively prevented the mobilization of calcium ions, ATP secretion, and serotonin release while thromboxane B2 levels did not change. Moreover, GJ inhibited the inside-out and outside-in signaling of integrin αIIbβ3. Notably, GJ treatment led to elevated expression of cyclic guanine monophosphate (GMP) (but not cyclic adenosine monophosphate). The protein expressions in the PI3K/Akt pathway were inhibited and platelet shape change was prevented. Finally, GJ treatment resulted in a decreased population of PNAs in vivo.DiscussionGJ exhibits potent anti-platelet activity acting by upregulating cGMP. It holds promise as a potential candidate for supplementation in patients with cardiovascular disease and thrombosis.